Regular and Young Investigator Award Abstracts 2022
DOI: 10.1136/jitc-2022-sitc2022.0194
|View full text |Cite
|
Sign up to set email alerts
|

194 Pre-clinical development of CT-1119, a mesothelin targeting chimeric antigen receptor macrophage (CAR-M), for solid tumor immunotherapy

Abstract: Background Despite significant success in treating hematological malignancies, adoptive cell therapies have yielded limited efficacy in solid tumors. 1 Macrophages are myeloid cells of the innate immune system and are naturally recruited to solid tumors, 2 where they have the potential to phagocytose tumor cells, activate the tumor microenvironment (TME), and prime a broad anti-tumor adaptive immune response via T cell recruitment and activation. We have previously developed chimeric antigen receptor macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Moreover, it has been observed that CAR-1119 substantially decreases tumor load in vivo , as evidenced by mouse xenograft models of lung cancer. 249 CT-0729 targets PSMA for the treatment of metastatic CRPC. In addition, MCY-M11 is a mesothelin-targeting CAR developed by MaxCyte that uses mRNA transfection of peripheral blood mononuclear cells (precursors of macrophages) to express CAR-M cells.…”
Section: Therapeutics Targeting Tamsmentioning
confidence: 99%
“…Moreover, it has been observed that CAR-1119 substantially decreases tumor load in vivo , as evidenced by mouse xenograft models of lung cancer. 249 CT-0729 targets PSMA for the treatment of metastatic CRPC. In addition, MCY-M11 is a mesothelin-targeting CAR developed by MaxCyte that uses mRNA transfection of peripheral blood mononuclear cells (precursors of macrophages) to express CAR-M cells.…”
Section: Therapeutics Targeting Tamsmentioning
confidence: 99%
“…Prior works have engineered monocytes to ameliorate immunosuppression through the secretion of inflammatory cytokines such as interferon (IFN)-𝛼 and interleukin (IL)-12; however, more recent strategies engineered monocytes to express HER2-targeted CAR, allowing monocytes to directly kill tumor cells in vitro and in vivo in an antigenspecific manner. [22][23][24][25][26] Although this therapy route is nascent and under preclinical development, it highlights the opportunity for CAR monocytes as a new therapeutic modality to treat solid tumor malignancies.…”
Section: Introductionmentioning
confidence: 99%